Tinjauan Tentang Perjanjian Hutang - Piutang Non Kontraktual Dengan Jaminan Gadai ( Studi Kasus Di Sukoharjo ) - Wicaksono, Andika Andrianus Wilham; , Septarina Budiwati, SH., MH (2016)
This study aims to determine how the construction of law, to know the legal protection for the parties, and to know the problems arising from indeptedness of agreement with a non-contractual agreement collateral in Mantung, Sukoharjo, Central Java. Method of this research is Juridical empirical with descriptive research. The data source are primary and secondary data, primary is the result of interviews and secondary data is primary and secondary data law. the techniques of collecting data are observation and interviews also analyzed qualitatively. The result of this research shows the indeptedless of agreement made in Mantung, Sukoharjo, Central Java that is an agreement to be made orally (non-contractual), allowed by the legislation Jo regrading 1338 and 1320 and 1150 KUHPerdata. Verbal agreement is allowed if can be done with good attitudes. Legal protection for the parties to do with legal protection preventive and repressive protection. The problems that arise are creditors rent guarantees to others.